WOMAN PRENEURSHIP APPROACH IN TRADITIONAL MARKET CULTURE (International Conference of Graduate School on Sustainability (ICGSS), 2018)
The existence of women as the drivers of the people's economy continues to stretch as an inseparable part of the market community. The connection is very close in realizing the economic order in the family sphere to build strong self-confidence, and prove that women are able to obtain results for the efforts that have been carried out. At present, stretching women in developing the economy in the traditional market environment can be proven from the way when starting a routine to end the routine as an economic actor and there is active involvement from other people. An entrepreneur woman is someone who is able to see business opportunities, struggle and be able to take into account all risks. This paper will present the results of the study regarding the existence of women as economic drivers in traditional market environments with all their dynamics, especially in building communication with market communities. A series of speech acts and communication skills with their characteristics can be a magnet for others to be involved in the process of buying and selling in the market. Owned motivation can improve welfare and strengthen participation in developing traditional market communities. The results show that the reality in traditional markets shows conditions that bring together expertise and personal values and are firmly rooted as a market culture handed down from generation to generation. Women are able to show the characteristics of independence in carrying out roles both in the family environment and in the social environment. The thing that needs to be emphasized is the individual's responsibility to do all the routines inherent in him.